Gestational age and hospital admissions during childhood, the TIGAR study: a population-based, record linkage study in England - Coathup, VL; Boyle, E; Carson, C; Johnson, S; Kurinzcuk, J; Macfarlane, A; Petrou, S; Rivero-Arias, O; Quigley, M (BMJ, 2020)
Objectives: To explore the association between gestation at birth and hospital admissions to age 10 years and how admission rates change throughout childhood.